Can a 1-day clear liquid diet with a split -dose polyethylene glycol overcome conventional practice patterns during the preparation for screening colonoscopy? - Diğdem Özer Etik; Nuretdin Suna; Cemre Gündüz; Ahmet Bostan; Alperen Özdemir; Bade Yağmur Gürel; Ezgi Yenişekerci; Ahmet Sedat Boyacıoğlu (Turkish Journal of Gastroenterology, 2019)
Background/Aims: A successful screening colonoscopy is closely linked to the quality of a bowel preparation. In this study, we aimed to determine the impact of a 1-day clear liquid diet (CLD) compared to a 3-day combined diet (CMD) accompanied by a split-dose regimen of polyethylene glycol and electrolyte lavage solution (PEG-ELS) for screening colonoscopy. Materials and Methods: This was a prospective, randomized, endoscopist-blinded study. Patients referred for screening colonoscopy were randomized to four groups as a 1-day CLD+PEG-ELS vs. a 1-day CLD+sulfate free (SF)-PEG-ELS and a 3-day CMD+PEG-ELS vs. a 3-day CMD+SF-PEG-ELS. An assessment of the quality of colon cleaning, tolerability to the preparation, and symptoms related to the preparation were recorded. Results: A total of 506 patients were enrolled in this study. The quality of bowel preparation was significantly inferior in the CMD+PEG-ELS group than CLD+PEG-ELS (p=0.004) and CMD+SF-PEG-ELS groups (p=0.007). There were no statistical differences among the groups in terms of the polyp detection rate. With respect to an easy rating of diet following and the consumption of laxative, there were no significant differences among the four groups. Gastric fullness and nausea/vomiting were pointed out much more, especially in the SF-PEG-ELS users (p=0.008 and p=0.004, respectively). Conclusion: A 1-day CLD was not inferior to a 3-day CMD for colonoscopy preparation in terms of bowel cleaning, the polyp detection rate, and patient tolerance. Cite this article as: Özer Etik D, Suna N, Gündüz C, et al. Can a 1-day clear liquid diet with a split -dose polyethylene glycol overcome conventional practice patterns during the preparation for screening colonoscopy? Turk J Gastroenterol 2019; 30(9): 817-25.